Ruang Konflik di Area Tapal Batas Indonesia-Timor Leste: Studi Kasus di Kabupaten Timor Tengah Utara dan Distrik Oecusse - Handrianus Nino (Sociology Department, Brawijaya University, 2018)
The border is the gate of the state which at the same time becomes an international door between one country and another, therefore it is appropriate if the border region becomes the face of the country concerned. But this does not appear in the reality of the people in the North Central Timor Regency who are directly adjacent to the Republic of Timor Leste's Democratic Republic of Timor because of the reality of the diverse social conflicts found there. Therefore, this paper discusses the dynamics of the conflict that occurred in the border region between Indonesia and the Democratic Republic of Timor Leste in relation to the boundary conflict between the two countries. By using the social conflict theory proposed by Ralf Dahrendorf and Lewis Coser, researchers tried to explore the reality of social conflict in the border region, by using a case study approach and qualitative methods, it was concluded that the reality of existing social conflicts based on interviews found indications of conflict. structural and functional because of conflicts that occur because the government does not involve community elements in issuing policies so that the establishment of boundaries is not in line with the expectations of the community, causing conflict between the two groups in the border region, namely the people in six villages in Timor Regency North Central with people in the Oecusse District.